Strategi Pengembangan Usaha Bumdes Di Desa Padang Beriang Kecamatan Pino Raya Periode 2017-2022 - Deko Agenty Putra; Siti Hanila; Yudi Irawan Abi (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2023)
This study aims to find out BUMDes business development strategy in Padang Beriang Village of Pino Raya Sub-District in period of 2017-2022. The sample in this study consisted of 30 people consisting of 8 village officials, 5 BUMDes managers in Padang Beriang Village of Pino Raya Sub-District, for the period of 2017-2022 for internal factors and 17 people for external factors, namely the local community in Padang Beriang Village of Pino Raya Sub-District. The analytical method used is SWOT analysis which consists of an Internal Strategic Factor Matrix (IFAS) and an External Strategic Factor Matrix (EFAS). The results of the study show that the BUMDes Business Development Strategy in Padang Beriang Village of Pino Raya Sub-District for the period of 2017-2022 supports the Aggressive strategy, or the SO strategy in the SWOT Matrix. The result of the sum of the strengths possessed is 18.9 while the weaknesses are 14.46, therefore, the internal factor quadrant is 18.9 – 14.46 = 4.44 which means the ability of the BUMDes business in Padang Beriang Village of Pino Raya Sub-District in utilizing strengths and minimizing weaknesses in the company's internal The opportunities that this strategy has are 21.15 and the threats are 17.52. Therefore, the external factor quadrant is 21.15 – 17.52 = 3.63 meaning the ability of BUMDes businesses in Padang Beriang Village of Pino Raya Sub-District, to take advantage of opportunities and overcome threats faced by companies in BUMDes business development.